Business Plan of “Nokase” – An Omakase restaurant with the Concept of Nordic x Asian - Nguyen, Thi Xuan Mai; Kubíček, Aleš; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The aim of this bachelor thesis is to present the business plan for Nokase, which identified as a restaurant in Prague with the blending concept of fusion cuisine of Japanese Omakase highlighted by Nordic cuisine. Despite the global popularity of Japanese food, the concept of Omakase remains quite rare in Prague. Nokase targets the market which seeking novelty and innovation in culinary landscape. The thesis is divided into two main parts. The theoretical part provides an overview of the culinary industry, and the methods and tools used for analysis including Business Model Canvas, PEST analysis, Porter’s Five Forces, Competitive Strategy, and SWOT . The practical part applies the frameworks and methods to business model of Nokase and includes the operational plan which outlines the practical implementation of the business strategy, as well as the financial analysis to assess its feasibility.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses